Interdependence in Water Resource Development in the Ganges : An Economic Analysis - Wu, Xun (IWA Publishing, 2016)
It is often argued that the true benefits of water resource development in international river basins are undermined by a lack of consideration of interdependence in water resource planning. Yet it has not been adequately recognized in the water resources planning literature that overestimation of interdependence may also contribute to lack of progress in cooperation in many systems. This paper examines the nature and degree of economic interdependence in new and existing water storage projects in the Ganges River basin based on analysis conducted using the Ganges Economic Optimization Model. We find that constructing large dams on the upstream tributaries of the Ganges would have much more limited effects on controlling downstream floods than is thought and that the benefits of low-flow augmentation delivered by storage infrastructures are currently low. A better understanding of actual and prospective effects of interdependence not only changes the calculus of the benefits and costs of different scenarios of infrastructure development, but might also allow riparian countries to move closer to benefit sharing positions that are mutually acceptable.